Variation in Inpatient Hospital Prices and Outpatient Service Quantities Drive Geographic Differences in Private Spending in Texas. (12th June 2014) - Franzini, Luisa; White, Chapin; Taychakhoonavudh, Suthira; Parikh, Rohan; Zezza, Mark; Mikhail, Osama
<x xml:space="preserve">Abstract</x> Objective To measure the contribution of market‐level prices, utilization, and health risk to medical spending variation among the Blue Cross Blue Shield of Texas (BCBSTX) privately insured population and the Texas Medicare population. Data Sources Claims data for all BCBSTX members and publicly available CMS data for Texas in 2011. Study Design We used observational data and decomposed overall and service‐specific spending into health status and health status adjusted utilization and input prices and input prices adjusted for the BCBSTX and Medicare populations. Principal Findings Variation in overall BCBSTX spending across HRRs appeared driven by price variation, whereas utilization variation factored more prominently in Medicare. The contribution of price to spending variation differed by service category. Price drove inpatient spending variation, while utilization drove outpatient and professional spending variation in BCBSTX. The context in which negotiations occur may help explain the patterns across services. Conclusions The conventional wisdom that Medicare does a better job of controlling prices and private plans do a better job of controlling volume is an oversimplification. BCBSTX does a good job of controlling outpatient and professional prices, but not at controlling inpatient prices. Strategies to manage the variation in spending may need to differ substantially depending on the service and payer.